(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The use of various types of radioactive drugs has increased the effectiveness of nuclear medicine. Technetium-99m (99mTc) radiopharmaceuticals are in widespread use owing to the availability and affordability of 99Mo/99mTc generators and the variety of kits for formulating the desired products. Together, they provide an array of specific tools for diagnosing a large number of diseases affecting the Heart, Kidney and major organs of the body such as the bones, brain, liver, parathyroid, and thyroid. Nuclear medicine requires high quality radiopharmaceuticals and kits that are safe for administration and efficacious for a given application. Since radiopharmaceuticals are intended for human use, it is imperative that they undergo quality control measure.This paper presents various parameters affecting labeling efficiency of radiopharmaceuticals and describes the procedures of preparing from four selected kits. Details of the ingredients are also included. The procedures described here can be used to develop manuals and standard operating procedures in Egypt. This study is expected to serve as a guide to radiopharmaceutical manufacturing centers of such kits. Four kits namely: MIBI, DTPA, MDP, and DMSA are used. Paper Chromatography was involved to disparate the polar and non-polar part of the kit-solution. Quality control testing assures purity, integrity, potency, product identity, biological safety and efficacy of radiopharmaceuticals. The success of diagnostic radiopharmaceutical has been reflected in the quality of images of diseased site.